2017
DOI: 10.19030/jabr.v34i1.10093
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of The Joint Provision Of Non-Audit Services On Audit Firm’s Tenure: A Kuwaiti Evidence

Abstract: Concerns about the potential harm of the increased economic bond between the audit firm and the audit client resulting from the joint provision of audit and NAS have been investigated extensively in the audit literature. However, much of this research was conducted in developed countries’ settings, with very little, if any, carried out in the context of a developing country. The current study aims at filling this gap in audit research by investigating two important issues related to the joint provision using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the other hand, practitioners, especially the Big Four, are still defending the provision of non-audit services and "are adamant that investor concerns over their non-audit earnings from [their] audit clients are completely unwarranted" (Nixon, 2004, p. 34). In line with practitioners' arguments, other studies found no negative relationship between non-audit services and audit performance especially when the company monitors the provision of NAS (Craswell et al, 2002;Al-Hajri 2018;Sharma & Sidhu 2001;McMillan 2004;Zhang et al, 2016;Wang & Hay 2013). Therefore, disclosing pre-approved non-audit services by the company audit committees implies two valuable messages to owners, the first one is the positive side of disseminating clear, detailed, and transparent information regarding both audit and non-audit services, the second message conveyed is that certifying members of the audit committee declare they have reviewed and scrutinised non-audit services before giving approval, and thus they provide reassuring message that there is no conflict of interest due to performing non-audit services.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 55%
“…On the other hand, practitioners, especially the Big Four, are still defending the provision of non-audit services and "are adamant that investor concerns over their non-audit earnings from [their] audit clients are completely unwarranted" (Nixon, 2004, p. 34). In line with practitioners' arguments, other studies found no negative relationship between non-audit services and audit performance especially when the company monitors the provision of NAS (Craswell et al, 2002;Al-Hajri 2018;Sharma & Sidhu 2001;McMillan 2004;Zhang et al, 2016;Wang & Hay 2013). Therefore, disclosing pre-approved non-audit services by the company audit committees implies two valuable messages to owners, the first one is the positive side of disseminating clear, detailed, and transparent information regarding both audit and non-audit services, the second message conveyed is that certifying members of the audit committee declare they have reviewed and scrutinised non-audit services before giving approval, and thus they provide reassuring message that there is no conflict of interest due to performing non-audit services.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 55%